The adventures of Mark Twain [videorecording (DVD)] - Vinton, Will; Twain, Mark, 1835-1910; Whitmore, James, 1921-2009 (Magnolia Home Entertainment, 2012)
Tom Sawyer, Huck Finn and Becky Thatcher stow away with Mark Twain on his magical airship and take an incredible journey through time in search of Halley's Comet. Along the way they encounter a variety of Twain's storybook characters.